Trouble in Paradise : Twenty-Four Essays on the Social History of American Art - Wallach, Alan, (Historical Materialism Book Series ;, 2025)
A collection of highly readable critical essays (1977-2023) by a leader in the field of American social art history. Among the subjects Alan Wallach explores are the art of Thomas Cole, patronage of the Hudson River School, so-called "Luminism," the rise of the American art museum, the historiography of American art, scholarship and the art market, as well as the work of Augustus Saint-Gaudens, Rockwell Kent, Grant Wood, Philip Evergood, and Norman Rockwell. Throughout, Wallach employs a materialist approach to argue against traditional scholarship that considered American art and art institutions in isolation from their social, historical, and ideological contexts. See Less